2015
DOI: 10.1016/j.difgeo.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Natural operations on differential forms

Abstract: MSC: 58Axx 58A32 53C05 Keywords: Natural operations Chern-Weil formsWe prove that the only natural operations between differential forms are those obtained using linear combinations, the exterior product and the exterior differential. Our result generalises work by Palais [8] and Freed-Hopkins [2].As an application, we also deduce a theorem, originally due to Kolář [3], that determines those natural differential forms that can be associated to a connection on a principal bundle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The proof closely follows the one given in [10] for the case of differentiable manifolds, which, in turn, applies techniques already used by the Czech school ( [7], [8]).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The proof closely follows the one given in [10] for the case of differentiable manifolds, which, in turn, applies techniques already used by the Czech school ( [7], [8]).…”
Section: Introductionmentioning
confidence: 78%
“…Quite recently, there have been a couple of reformulations of this result ( [6], [10]) that, essentially, confirm that the only natural operation between differential forms is the exterior differential. These theorems have been used for several different applications ( [4], [6], [9], [10], [15]). As an example, these ideas have been succesfully extended to study differential operations on forms on contact manifolds, allowing a deeper understanding of the Rumin operator ( [2]).…”
Section: Introductionmentioning
confidence: 88%
“…More general operations in a much broader context are studied in [KMS93], but the operations relevant to us are still linear (and we are interested in nonlinear ones as well); there it is shown that all operations that raise the form degree by one are multiples of the exterior derivative, and linearity follows from naturality. More recently, operations (both linear and nonlinear) acting on 1-forms (connections) were considered in [FH13], and generalized to differential forms of all degrees in [NS15]. We will make use of this for our construction of cohomology operations on closed differential forms Ω * cl in stacks.…”
Section: Introductionmentioning
confidence: 99%
“…Again, more operators appear, for instance ω → ω ∧ ω or ω → ω ∧ P a,i ω ∧ dω. Using the Peetre-Slovák theorem as in [19], one can show that a natural operator (satisfying an additional regularity assumption) on ContMan 2n+1 must be a differential operator. We do not have a complete description of these operators.…”
Section: Introductionmentioning
confidence: 99%
“…We do not have a complete description of these operators. v) One could also, as in [19], consider natural operations on k-tuples of forms. There are many of them, for instance (ω 1 , ω 2 ) → P a 1 +a 2 ,i (ω 1 ∧ ω 2 ) or (ω 1 , ω 2 ) → d(ω 1 ∧ P a 2 ,i ω 2 ).…”
Section: Introductionmentioning
confidence: 99%